Schülervorstellungen zur Plattentektonik – Ergebnisse einer qualitativen Interviewstudie mit Schülerinnen und Schülern der neunten Jahrgangsstufe - Conrad, Dominik (Journal of Geography Education, 2015)
Fifteen 9th grade students aged 14-15 of four different Bavarian grammar schools have been interviewed on the topic of plate tectonics using semi-structured interviews. The theoretical framework for this study is based on the theory of experientialism. Interviews have been analyzed by a combination of qualitative content analysis, systematic metaphor analysis and a systematic analysis of gesture. By this means I could identify students' central conceptions as well as the source domains used by students to construct these conceptions. Main results of the study show that students associate plates strongly with continents and far less with oceanic floor. Students use many elements from an everyday-life conception of a plate to understand tectonic plates. They are only aware of horizontal movements of plates, but they do not consider the possibility of destruction and production of lithosphere at the plates' borders. According to the students conceptions the rotation of the earth, earth's core, rivers of magma inside the earth, earth's gravitational force or natural phenomena like earthquakes cause plates' movements. For explaining causes of plates' movement students use everyday-life experiences with movements as source domains. Some students think plates' moving is caused by pushing or pulling forces, other students belief plates are transported or they slip down a slope.
Keywords: student conceptions, plate tectonics, theory of experientialism, systematic metaphor analysis, gestures